Evaluation of tween 80 incorporated media to increase pathogen isolation from peritoneal fluid of CAPD patients at a public hospital in Kuala Lumpur, Malaysia - Ganapathy Pillay, Stella (2020)
Continuous ambulatory peritoneal dialysis (CAPD) is a reliable and costeffective method that offers the advantage of greater higher molecular-weight substances clearance compared to hemodialysis. However, peritonitis remains a major complication that leads to increased morbidity and mortality in CAPD patients. Although a successful diagnosis of peritonitis highly depends on the isolation of pathogens, in routine microbiology laboratory practices, identification of pathogen is being a great challenge due to high rate of culture-negative peritonitis. In order to reduce the incidence rate of culturenegative among the CAPD patients, this study was aimed to evaluate and optimize the performance of Tween 80 incorporated media at three different concentrations (0.1%, 1% and 2%). Of the 121 peritoneal fluid samples collected from CAPD patients suspected for peritonitis between September 2018 to June 2019 at Hospital Kuala Lumpur, 109 patients (90.1%) were showed to be fulfilling the criteria for peritonitis proposed by International Society for Peritoneal Dialysis (ISPD) guidelines. Among the seven different culture media used, including Tween 80 incorporated blood agar at three different concentrations, blood agar without Tween 80, MacConkey agar, Sabouraud’s dextrose agar and brain heart infusion agar, Tween 80 incorporated blood agar yielded the highest positive culture (23/121) than all the other standard media. The analysis by Chi Square revealed significant difference (p <0.001) between the three concentrations of Tween 80 tested in this study. Among the three concentrations optimized, Tween 80 incorporation at 0.1% has been the best concentration that support the optimum growth of all Gram-positive organisms, Gram-negative organisms and yeast cells simultaneously. The utilization of broad-range PCR using 16S rRNA typing and 5.8S rRNA typing for both bacteria and fungi identification has significantly increased the positive rate from 15.7% by culture method to 22.3% by molecular identification. Four additional bacterial species and one additional fungi was identified by molecular method in comparison with culture method. The utilization of gene sequencing has improved the rapid identification of pathogens in culture-negative samples suspected for peritonitis. However, due to cost constraint as a major limitation in many hospitals, conventional culture method is still preferred to be the cost-effective and reliable identification method for the management of CAPD associated peritonitis. The combination of culture and molecular method has revealed that, the occurrence of Grampositive bacterial peritonitis (69.6%) was the highest followed by Gramnegative bacterial peritonitis (21.8%) and fungal peritonitis (8.6%) in CAPD patients. Majority of the pathogen recovery by both molecular and culture methods were found to be similar in identification. Therefore, Tween 80 incorporated media has provided satisfactory result in the management of peritonitis diagnosis. In conclusion, this study suggest that the Tween 80 incorporated media at 0.1% concentration has the potential to be used as a single medium for the optimum isolation of pathogens in CAPD peritonitis. The molecular method can be used as a supplementary test to support the culture result and not as a standalone test for pathogen identification due some limitations. This approach can be applied in all diagnostic laboratories, particularly in resources-limited settings to enhance the yield of pathogens in CAPD associated peritonitis.